Answer: 10 is your answer bud ❤
(2x + 2) = (3x + -52)
Reorder the terms:
(2 + 2x) = (3x + -52)
Remove parenthesis around (2 + 2x)
2 + 2x = (3x + -52)
Reorder the terms:
2 + 2x = (-52 + 3x)
Remove parenthesis around (-52 + 3x)
2 + 2x = -52 + 3x
Solving
2 + 2x = -52 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
2 + 2x + -3x = -52 + 3x + -3x
Combine like terms: 2x + -3x = -1x
2 + -1x = -52 + 3x + -3x
Combine like terms: 3x + -3x = 0
2 + -1x = -52 + 0
2 + -1x = -52
Add '-2' to each side of the equation.
2 + -2 + -1x = -52 + -2
Combine like terms: 2 + -2 = 0
0 + -1x = -52 + -2
-1x = -52 + -2
Combine like terms: -52 + -2 = -54
-1x = -54
Divide each side by '-1'.
x = 54
Simplifying
x = 54
Answer:
rational. both numbers are whole numbers.
Step-by-step explanation:
Answer:
Step-by-step explanation:
(number of sides-2)*180 = (6-2)*180 = 720°
a= 720/6= 120°
lines form 180° angles
b= 180-120= 60°
sum of angles in a triangle is 180, and the angles are ≡
c=180/3 = 60°
c and d are supplementary angles (they add to 180)
d= 180-60 = 120°
d ≡ e+e because are vertical angles
e= 120/2 = 60°
sum of angles in a triangle is 180
f= 180 -90-60 = 30°
(number of sides-2)*180 = (5-2)*180 = 540°
g= 540/5= 108°
Answer:
<h3>9.n 4</h3><h3>10.x -1</h3><h3>11.4x 4</h3><h3>12.p -1</h3>
I hope this helps:D